“Making Cool Things Hot Again”: Blackface and Newfoundland Mummering - Best, Kelly (Ethnologies)

(untitled) (Association Canadienne d'Ethnologie et de Folklore, 2008)
This article critically examines instances of blackface in Newfoundland Christmas mummering. Following Peter Narváez’s call for analysis of expressive culture from folklore and cultural studies approaches, I explore the similarities between these two cultural phenomena. I see them as attempts to work out racial and class tensions among the underclasses dwelling in burgeoning seaport towns along the North American seaboard that were intimately connected, at that time, through heavily-trafficked shipping routes. I offer a reanalysis of the tradition that goes beyond unconscious, symbolic ritualism to one that examines mummering in a historical context. As such, I present evidence which troubles widely held understandings of Christmas mummering as an English-derived calendar custom.